Direct stimulation of receptor-controlled phospholipase D1 by phospho-cofilin - Han, Li; Stope, Matthias B; de Jesús, Maider López; Oude Weernink, Paschal A; Urban, Martina; Wieland, Thomas; Rosskopf, Dieter; Mizuno, Kensaku; Jakobs, Karl H; Schmidt, Martina (The EMBO journal, 2007)
The activity state of cofilin, which controls actin dynamics, is driven by a phosphorylation–dephosphorylation cycle. Phosphorylation of cofilin by LIM‐kinases results in its inactivation, a process supported by 14‐3‐3ζ and reversed by dephosphorylation by slingshot phosphatases. Here we report on a novel cellular function for the phosphorylation–dephosphorylation cycle of cofilin. We demonstrate that muscarinic receptor‐mediated stimulation of phospholipase D1 (PLD1) is controlled by LIM‐kinase, slingshot phosphatase as well as 14‐3‐3ζ, and requires phosphorylatable cofilin. Cofilin directly and specifically interacts with PLD1 and upon phosphorylation by LIM‐kinase1, stimulates PLD1 activity, an effect mimicked by phosphorylation‐mimic cofilin mutants. The interaction of cofilin with PLD1 is under receptor control and encompasses a PLD1‐specific fragment (aa 585–712). Expression of this fragment suppresses receptor‐induced cofilin–PLD1 interaction as well as PLD stimulation and actin stress fiber formation. These data indicate that till now designated inactive phospho‐cofilin exhibits an active cellular function, and suggest that phospho‐cofilin by its stimulatory effect on PLD1 may control a large variety of cellular functions.